Outcomes of retreatment after hyperopic laser in situ keratomileusis. Issue 11 (November 2017) - Frings, Andreas; Intert, Elisa; Steinberg, Johannes; Druchkiv, Vasyl; Linke, Stephan J.; Katz, Toam
Abstract : Purpose : To evaluate the efficacy, predictability, and safety of laser in situ keratomileusis (LASIK) retreatment in eyes with hyperopia. Setting : Multicenter refractive surgery centers and University Hospital, Germany. Design : Retrospective case series. Methods : This multicenter study included hyperopic patients with a preoperative difference between cycloplegic and manifest refraction of 1.00 diopter (D) or less who had LASIK retreatment based on manifest refraction. The refractive outcome was analyzed according to standard graphs for reporting the efficacy, predictability, and safety of refractive surgery. Results : One hundred thirteen eyes of 113 consecutive hyperopic patients were enrolled. Efficacy ( P < .001) and safety ( P = .004) were statistically significantly improved by retreatment without being negatively influenced by preoperative manifest spherical equivalent (SE), manifest cylinder, or keratometry. In cases still showing a trend toward undercorrection, retreatment resulted in 88 eyes (78.0%) being within ±0.50 D of the attempted correction. The optical zone (OZ) diameter of the retreatment did not correlate with efficacy, predictability, or safety. Conclusions : Retreatment after hyperopic LASIK resulted in high efficacy, predictability, and safety outcomes. The efficacy and safety of the retreatment were not affected by preoperative manifest SE, manifest cylinder, keratometry, or OZ diameter.